2010
DOI: 10.1002/pbc.22640
|View full text |Cite
|
Sign up to set email alerts
|

Traditional laboratory measures of cardiovascular risk in hereditary spherocytosis

Abstract: Background Individuals who have undergone splenectomy may be at an increased risk of arterial and venous thrombosis. We sought to determine if splenectomy affects surrogate laboratory measures of cardiovascular risk in persons with hereditary spherocytosis (HS). Procedure We conducted a prospective cross-sectional study of 21 children and 36 adults with HS. Fasting blood samples were collected for complete blood count and plasma lipid panel, homocysteine, lipoprotein (a), C-reactive protein, and fibrinogen. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
8
0
7

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 46 publications
3
8
0
7
Order By: Relevance
“…For HS, all types of splenectomy resulted in control of clinical symptoms as well as improvement in hematologic laboratory parameters. Although our registry did not compare outcomes between PS and TS, both procedures had improved hematologic outcomes after surgery, a finding consistent with most previous literature [3, 4, 14, 18, 19]. A prospective randomized clinical trial will be required to definitively compare surgical procedures or surgical vs medical therapies.…”
Section: Discussionsupporting
confidence: 57%
“…For HS, all types of splenectomy resulted in control of clinical symptoms as well as improvement in hematologic laboratory parameters. Although our registry did not compare outcomes between PS and TS, both procedures had improved hematologic outcomes after surgery, a finding consistent with most previous literature [3, 4, 14, 18, 19]. A prospective randomized clinical trial will be required to definitively compare surgical procedures or surgical vs medical therapies.…”
Section: Discussionsupporting
confidence: 57%
“…Crary et al have reported reduced total cholesterol and LDL-C levels in patients with HS and an intact spleen. They found higher cholesterol levels in splenectomized patients, though within normal limits [26]. We did not observe an abnormal lipid profile in our patients.…”
Section: Discussionsupporting
confidence: 49%
“…Elevated fibrinogen predicts ischemic stroke and advanced atherosclerosis [34,35]. Crary et al [26] reported significantly raised fibrinogen [38]. However, none of our patients had elevated fibrinogen.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations